Fluvial Depositional Systems of the African Humid Period: An Analog for an Early, Wet Mars in the Eastern Sahara. Issue 5 (13th May 2022) - Zaki, A. S.; Davis, J. M.; Edgett, K. S.; Giegengack, R.; Roige, M.; Conway, S.; Schuster, M.; Gupta, S.; Salese, F.; Sangwan, K. S.; Fairén, A. G.; Hughes, C. M.; et al.
Abstract: A widely hypothesized but complex transition from widespread fluvial activity to predominantly aeolian processes is inferred on Mars based on remote sensing data observations of ancient landforms. However, the lack of analysis of in situ martian fluvial deposits hinders our understanding of the flow regime nature and sustainability of the martian fluvial activity and the hunt for ancient life. Studying analogs from arid zones on Earth is fundamental to quantitatively understanding geomorphic processes and climate drivers that might have dominated during early Mars. Here we investigate the formation and preservation of fluvial depositional systems in the eastern Sahara, where the largest arid region on Earth hosts important repositories of past climatic changes. The fluvial systems are composed of well‐preserved single‐thread sinuous to branching ridges and fan‐shaped deposits interpreted as deltas. The systems' configuration and sedimentary content suggest that ephemeral rivers carved these landforms by sequential intermittent episodes of erosion and deposition active for 10–100s years over ∼10, 000 years during the late Quaternary. Subsequently, these landforms were sculpted by a marginal role of rainfall and aeolian processes with minimum erosion rates of 1.1 ± 0.2 mm/yr, supplying ∼96 ± 24 × 10 10  m 3 of disaggregated sediment to adjacent aeolian dunes. Our results imply that similar martian fluvial systems preserving single‐thread, short distance source‐to‐sink courses may have formed due to transient drainage networks active over short durations. Altogether, this study adds to the growing recognition of the complexity of interpreting climate history from orbital images of landforms. Plain Language Summary: Mars is currently a dry and cold desert, but rivers preserved in inverted topography suggest that water once flowed during its early history. However, how sustained and how frequently these rivers flowed remains uncertain. Here we study ancient fluvial systems (rivers and deltas) from the eastern Sahara that formed during the late Quaternary, in much wetter conditions than those prevailing today in this desert and which bear striking analogies to martian systems. We find that rivers and deltas, now preserved as ridges, record short distance source‐to‐sink high‐energy systems formed due to heavy rainfall events. Our observations and measurements of the meandering systems within the deltaic features suggest that such wet conditions might have spanned tens to a few hundred years over a total duration of ∼10, 000 years. Since the wet conditions ceased, arid conditions prevailed, and the aeolian processes resumed, sculpting ridges out of ancient channels. Our results imply that martian fluvial systems may have been associated with similar local and heavy runoff conditions that lasted 10–100s years over thousands of years, possibly sufficient to support habitability. A shift toward arid environments led to the sculpting of fluvial ridges and the widespread formation of dunes across the modern martian landscape. Key Points: Ancient depositional rivers in southern Egypt record ephemeral fluvial systems formed due to intense rainfall over ∼10 ka These fluvial systems suggest tens to hundreds of years of river activity Similar martian systems imply that early Mars's surface was punctuated by local and transient drainage systems fed over short durations